2014
DOI: 10.1111/dgd.12154
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and dynamic type II cadherin expression associated with development of the primate visual system

Abstract: The middle temporal visual area (MT, also known as V5) is a visual association area that is particularly evolved in the primate brain. The MT receives input from the primary visual area (V1), constitutes part of the dorsal visual pathway, and plays an essential role in processing motion. Connections between the MT and V1 in the primate brain are formed after birth, and are related to the maturation of visual system. However, it remains to be determined what molecular mechanisms control the formation and matura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…The Cdh12 expression in the middle layer (presumptive layer IV) was seen in the temporal or occipital NCX, as previously described (Matsunaga et al . ), but not in the parietal NCX. However, by the neonatal stage, Cdh12 expression in layer IV became clear in the parietal NCX (Matsunaga et al .…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The Cdh12 expression in the middle layer (presumptive layer IV) was seen in the temporal or occipital NCX, as previously described (Matsunaga et al . ), but not in the parietal NCX. However, by the neonatal stage, Cdh12 expression in layer IV became clear in the parietal NCX (Matsunaga et al .…”
Section: Resultsmentioning
confidence: 77%
“…We found that the expression of various cadherins differed between rodents and primates and was dynamically regulated, and in some cases, was related to the formation of primate‐specific visual circuits (Matsunaga et al . , ). Here, to explore whether primate specific expression of cadherins is seen even in the embryonic stage, we performed a more extensive spatial and temporal analysis of cadherin expressions in the developing embryonic NCX.…”
Section: Introductionmentioning
confidence: 99%
“…As an extension to the studies depicted in the previous section, shifts in cadherin expression patterns were detected between pulvino-MT and lateral geniculate nucleus (LGN)-V1 pathways and in the MT/V5 around the time of birth, which preceded the development of V1-MT connections, suggesting that a change in cadherin expression around the lateral sulcus may be a general mechanism to control neural plasticity in regard to higher cognitive abilities ( Fig. 5 in Matsunaga et al 2014).…”
Section: Body Axis Of Primates: Vertical Conversion Required Higher Smentioning
confidence: 63%
“…Considerable effort has been put into characterizing the identity of the intrinsic signals that control the development of the marmoset neocortex, with the ultimate goal to associate a specific sequence of genes with each neocortical area. Groups at the RIKEN have in particular been extremely active in this domain, publishing high‐quality expression profiles of many genes in the newborn and postnatal marmoset neocortex and thalamic relay nuclei (Mashiko et al, ; Matsunaga et al, ). The RIKEN is soon to release a comprehensive online anatomical resource compiling the expression profile of a vast number of genes, following the model of the Allen Brain Atlas, increasing the exposure of the marmoset as a model for developmental neuroscience (https://gene-atlas.bminds.brain.riken.jp/).…”
Section: Molecular Patterning Of the Neocortexmentioning
confidence: 99%